Fertilisation of semi-mature Pinus elliottii and Pinus elliottii x caribaea stands on a climatic gradient in the Tsitsikamma and its effect on system nutrition and stand productivity - Gerhardus Petrus, Scheepers (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.